Diagnostic, prognostic, and predictive importance of neutrophil/lymphocyte ratio (NLR), platelet/lymphocyte ratio (PLR), and CA125 in endometrial hyperplasia and carcinoma - Bharti Kumari; Debaditya Haldar; Guddi R. Singh; Sweta Kumari; Sangeeta Pankaj; Rajnikant Prasad (Wolters Kluwer Medknow Publications, 2024)
Background: Inflammation has an important role in the progression of endometrial carcinoma. Aims: The aim of this study is to find the association between neutrophil/lymphocyte ratio (NLR), platelet/lymphocyte ratio (PLR), and CA125 in endometrial hyperplasia and endometrial carcinoma. The study also focuses on the association of CA125, NLR, and PLR with histopathological parameters in endometrial carcinoma that are of prognostic importance. Materials and Methods: This is a prospective cross-sectional study on 57 biopsy-proven cases of endometrial hyperplasia and carcinoma conducted over a period of two years. The NLR, PLR, and CA125 were calculated and recorded in all the 57 cases. Results: The 57 cases were divided into three groups: endometrial hyperplasia without atypia group which included 36 cases, endometrial atypical hyperplasia group which included 10 cases, and the endometrial carcinoma group which included 11 cases. Comparison was done between the groups, and parity, NLR, PLR, and CA125 were found to be significant, but patient age and postmenopausal status were not significant. NLR, PLR, and CA125 were found to increase with higher grade, pT-stage, and nodal stage for the endometrial carcinoma cases. Conclusion: NLR, PLR, and CA125 were marginally increased or normal in the case of endometrial hyperplasia without atypia and endometrial atypical hyperplasia, while they were significantly increased in endometrial carcinoma, and also correlated with an increase in grade, pT-stage, and nodal stage. Hence, these can be considered for additional screening as diagnostic, prognostic, and predictive markers in case of abnormal uterine bleeding with endometrial pathology.